Tailored construction of one-dimensional TiO2/Au nanofibers: Validation of an analytical assay for detection of diphenylamine in food samples. (30th June 2022) - Kokulnathan, Thangavelu; Vishnuraj, Ramakrishnan; Chen, Shen-Ming; Pullithadathil, Biji; Ahmed, Faheem; Hasan, P.M.Z.; Bilgrami, Anwar L.; Kumar, Shalendra
Highlights: We fabricated 1D TiO2 /Au NFs via an electrospinning approach. A TiO2 /Au NFs/SPCE was successfully applied for electrochemical detection of DPA. The TiO2 /Au NFs/SPCE exhibits a LOD, good linear range and high selectivity. The practical applicability of TiO2 /Au NFs/SPCE for sensing of DPA in food samples. Abstract: We report a one-dimensional titanium dioxide encapsulated with gold heterojunction nanofibers (TiO2 /Au NFs) as robust electrocatalysts for electrochemical detection of diphenylamine (DPA). A TiO2 /Au NFs were successfully synthesized by a coaxial electrospinning method. The formation of TiO2 /Au NFs was confirmed by various analytical and spectroscopic approaches. The fabricated TiO2 /Au NFs modified screen-printed carbon electrodes (SPCE) exhibit a well-enhanced detection activity towards DPA sensing as compared to other electrodes. Under the experimental conditions, the proposed electrode leading to the sensing range from 0.05 to 60 µM with a detection limit of 0.009 µM was obtained for the DPA detection. Moreover, the TiO2 /Au NFs/SPCE showed good selectivity towards the electrochemical oxidation of DPA. Interestingly, the TiO2 /Au NFs modified electrode was then applied to detect the effect of DPA on spiked content in the food samples.